Childhood stress, grown-up brain networks: corticolimbic correlates of threat-related early life stress and adult stress response. Issue 7 (25th September 2017) - Kaiser, R. H.; Clegg, R.; Goer, F.; Pechtel, P.; Beltzer, M.; Vitaliano, G.; Olson, D. P.; Teicher, M. H.; Pizzagalli, D. A.
Abstract: Background: Exposure to threat-related early life stress (ELS) has been related to vulnerability for stress-related disorders in adulthood, putatively via disrupted corticolimbic circuits involved in stress response and regulation. However, previous research on ELS has not examined both the intrinsic strength and flexibility of corticolimbic circuits, which may be particularly important for adaptive stress responding, or associations between these dimensions of corticolimbic dysfunction and acute stress response in adulthood. Methods: Seventy unmedicated women varying in history of threat-related ELS completed a functional magnetic resonance imaging scan to evaluate voxelwise static (overall) and dynamic (variability over a series of sliding windows) resting-state functional connectivity (RSFC) of bilateral amygdala. In a separate session and subset of participants ( n = 42), measures of salivary cortisol and affect were collected during a social-evaluative stress challenge. Results: Higher severity of threat-related ELS was related to more strongly negative static RSFC between amygdala and left dorsolateral prefrontal cortex (DLPFC), and elevated dynamic RSFC between amygdala and rostral anterior cingulate cortex (rACC). Static amygdala-DLPFC antagonism mediated the relationship between higher severity of threat-related ELS and blunted cortisol response to stress, but increased dynamic amygdala-rACC connectivity weakened this mediated effect and was related to more positive post-stress mood. Conclusions: Threat-related ELS was associated with RSFC within lateral corticolimbic circuits, which in turn was related to blunted physiological response to acute stress. Notably, increased flexibility between the amygdala and rACC compensated for this static disruption, suggesting that more dynamic medial corticolimbic circuits might be key to restoring healthy stress response.